Enhanced production of 5-hydroxymethyl-2-furfurylamine from biobased HMF by a robust triple mutant ω-transaminase biocatalyst in a betaine:malonic acid − water medium. (1st July 2023) - Wu, Changqing; Li, Qing; Di, Junhua; He, Yu-Cai; Ma, Cuiluan
Graphical abstract: Highlights: 5-Hydroxymethyl-2-furfurylamine (HMFA) was biosynthesized from biobased HMF. The amination activity and thermostability of ω-transaminase mutant were improved. Betaine:malonic acid − water medium was used as catalyst and solvent for producing HMF. 900 mM HMF was aminated to HMFA in 97.4 % yield in betaine:malonic acid (5 wt%). An efficient chemoenzymatic process gave a productivity of 0.43 g HMFA/g fructose. Abstract: 5-Hydroxymethyl-2-furfurylamine (HMFA) is a key furan-based compound for manufacturing curing agents, additives, medicines and agrochemicals. It is also a good solvent for production of valuable biobased chemicals and biofuels. HMFA can be obtained by biological amination of 5-HMF by ω-transaminase (AT) from Aspergillus terreus . In this work, one stable triple mutant of AT ω-transaminase (HNILGD) was obtained via consensus mutagenesis. The half-life (t1/2 ) of the mutant AT ω-transaminase [G292D (glycine to aspartate), H210N (histidine to asparagine) I77L (isoleucine to leucine)] was 1.43- and 2.14-fold higher than that of the wild-type AT ω-transaminase at 35 °C and 50 °C, respectively. Recombinant E. coli containing HNILGD ω-transaminase could aminate high load of 5-HMF (800 mM) to HMFA in the aqueous media [HMFA yield 92 %, selectivity 100 %]. In deep eutectic solvent betaine:malonic acid (5 wt%), HNILGD cells converted 900 mM 5-HMF to HMFA with a yield of 97.4 %. Moreover, d - fructose was chemoenzymatically transformed to HMFA in the betaine:malonic acid − water. 36.0 g/L of d - fructose was dehydrated into 5-HMF (63.9 % yield) with betaine:malonic acid (5 wt%) at 180 °C for 1 h, and the formed 5-HMF was further aminated to HMFA by HNILGD cells with amine donor d - alanine ( d - Ala-to-5-HMF molar ratio 16:1) at 35 °C and pH 8.0 after 24 h in betaine:malonic acid (5 wt%), obtaining a productivity of 0.433 g HMFA per g d - fructose [cal. 0.96 g HMFA/(g d -fructose-derived 5-HMF)]. A significant enhancement of HMFA production from biobased d -fructose-derived HMF by a robust triple mutant ω-transaminase biocatalyst was successfully developed in a betaine:malonic acid − water system.